O-GlcNAcylation: roles and potential therapeutic target for bone pathophysiology - Xiaohan Yan; Jingjing Zheng; Wenhao Ren; Shaoming Li; Shuying Yang; Keqian Zhi; Ling Gao (Cell Communication and Signaling, 2024)
Abstract O-linked N-acetylglucosamine (O-GlcNAc) protein modification (O-GlcNAcylation) is a critical post-translational modification (PTM) of cytoplasmic and nuclear proteins. O-GlcNAcylation levels are regulated by the activity of two enzymes, O-GlcNAc transferase (OGT) and O‑GlcNAcase (OGA). While OGT attaches O-GlcNAc to proteins, OGA removes O-GlcNAc from proteins. Since its discovery, researchers have demonstrated O-GlcNAcylation on thousands of proteins implicated in numerous different biological processes. Moreover, dysregulation of O-GlcNAcylation has been associated with several pathologies, including cancers, ischemia-reperfusion injury, and neurodegenerative diseases. In this review, we focus on progress in our understanding of the role of O-GlcNAcylation in bone pathophysiology, and we discuss the potential molecular mechanisms of O-GlcNAcylation modulation of bone-related diseases. In addition, we explore significant advances in the identification of O-GlcNAcylation-related regulators as potential therapeutic targets, providing novel therapeutic strategies for the treatment of bone-related disorders.